Factors to be considered in the interpretation of inorganic phosphorus values in the blood serum of bovines - Dayrell, Milton de Souza; Lopes, Henrique O. da Silva; Sampaio, Ivan B. Machado; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
The factors studied included 1) the effects of temperature after collection of the blood sample, 2) the time interval between collection and separation of serum, 3) the effect of storage at room temperature and in refrigeration for differing periods of time, and 4) influence of different degrees of haemolysis on the inorganic phosphorus level. Inorganic phosphorus was also determined in plasma and whole blood, and the values were compared with those found Iii the serum. The inorganic phosphorus values were elevated significanty when the serum was separated after the blood had remained at room temperature for more than 3 hours; there was no significant difference when the serum was separated after the blood had been refrigerated for up to 24 hours. The phosphorus values were not altered when the serum was kept up to 7 days in the refrigerator, deep freezer, or at room temperature with one drop of formalin for each 3 ml of serum. Slight or moderate haemolysis did not, influence the serum inorganic phosphorus values, when the serum was separated within 24 hours after the collection of the blood. When serum with slight or moderate haemolysis was examined there was no difference because of storage for 7 days, of storage in the refrigerator or storage at room temperature with formalin. Serum with severe haemolysis had significantly higher phosphorus values following all three types of storage. Inorganic phosphorus estimation in the serum gave significantly higher values than those from plasma or whole blood, with a regression coefficient of Y (phosphorus of plasma) ═ -0.44 + 0.907 X (phosphorus of serum) and Y (phosphorus of serum) ═ 1.38 + 1.07 X (phosphorus of whole blood).